The Influence of Self-Development and Internship Experience on Job Readiness: A Quantitative Study in Indonesian Higher Education - Martiwi, Rini; Elyana, Instianti; Suardhita, Nyoman; Rahman, Aan (Manunggal Halim Jaya, 2025)
This study investigates the influence of self-development and internship experience on job readiness among students participating in the Certified Internship and Independent Study Program (MSIB) Batch 5. Employing a quantitative descriptive approach with a causal design, data were collected from 50 purposively selected students using a structured online questionnaire. The analysis, conducted using SPSS version 26, involved multiple linear regression, t-tests, and F-tests. Results indicate that both self-development and internship experience have a positive and statistically significant effect on job readiness, both individually and simultaneously. The two variables together account for 92% of the variance in job readiness, demonstrating a strong model fit. These findings support existing theories such as Maslow’s hierarchy of needs and self-efficacy theory, affirming the role of personal growth and experiential learning. Practically, the study underscores the need for higher education institutions and internship providers to integrate structured personal development and industry-aligned internship programs to enhance students’ career preparedness and smooth their transition into the workforce.